2018
DOI: 10.3233/jad-170679
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know About Behavioral Crises in Dementia? A Systematic Review

Abstract: Interventions to reduce the likelihood of people with dementia-related behaviors reaching crisis point need to focus on both family and care home settings and incorporate aggression and agitation management. Future research should focus on determining the factors that could be addressed to prevent behavioral crises and the interventions and models of care that may help to prevent crises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…7,8 However, up to 50% of persons living with dementia display paranoia or hallucinations 7 and most demonstrate behavioral and psychiatric symptoms in dementia. [2][3][4] Intoxication with alcohol is common among older adults with 9% qualifying as binge drinkers and 2%…”
Section: Causes Of Agitation In Older Adultsmentioning
confidence: 99%
“…7,8 However, up to 50% of persons living with dementia display paranoia or hallucinations 7 and most demonstrate behavioral and psychiatric symptoms in dementia. [2][3][4] Intoxication with alcohol is common among older adults with 9% qualifying as binge drinkers and 2%…”
Section: Causes Of Agitation In Older Adultsmentioning
confidence: 99%
“…51 A 2018 study into the factors associated with dementia-related behavioural crises found agitation and aggression to be the most commonly reported behavioural crisis, diminishing the quality of life of both people with dementia as well as their caregivers. 54…”
Section: Ad Treatments In Clinical Trialsmentioning
confidence: 99%
“…A mental health crisis often means that the person with dementia does not feel able to cope or be in control of a situation [ 1 ]. Several factors may be associated with an episode of crisis, such as difficult behaviours (e.g., agitation/aggression, delusions, wandering, dysphoria, resistance to care) and/or physical illness or stress in the carer [ 2 ]. When the crisis is not properly managed, it can lead to increased use of emergency care services and hospital or long-term care admission [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a difficult situation may be interpreted as critical by the carer and lead to a call for professional help, without necessarily being experienced as a crisis by the person with dementia. A crisis can resolve spontaneously (e.g., the feeling of loss experienced by a person with dementia may disappear when the carer is home) or remain unresolved even after professional input (e.g., the person may become aggressive towards the carer thinking that s/he is a stranger and this episode is repeated over time with no benefits experienced from either medication or aggression/agitation management plans) [ 2 ]. In the UK, multidisciplinary teams have been established as a secondary care service to avert crises.…”
Section: Introductionmentioning
confidence: 99%